Protection against oxidative stress in Escherichia coli stationary phase by a phosphate concentration-dependent genes expression - Schurig Briccio, Lici Ariane (2009)
Escherichia coli gradually decline the capacity to resist oxidative stress during stationary phase. Besides the aerobic electron transport chain components are down-regulated in response to growth arrest. However, we have previously reported that E. coli cells grown in media containing at least 37 mM phosphate maintained ndh expression in stationary phase, having high viability and low NADH/NAD+ ratio. Here we demonstrated that, in the former condition, other aerobic respiratory genes (nuoAB, sdhC, cydA, and ubiC) expression was maintained. In addition, reactive oxygen species production was minimal and consequently the levels of thiobarbituric acid-reactive substances and protein carbonylation were lower than the expected for stationary cells. Interestingly, defense genes (katG and ahpC) expression was also maintained during this phase. Our results indicate that cells grown in high phosphate media exhibit advantages to resist endogenous and exogenous oxidative stress in stationary phase.